2020
DOI: 10.1177/1362361320933048
|View full text |Cite
|
Sign up to set email alerts
|

Temperament influences the relationship between symptom severity and adaptive functioning in children with autism spectrum disorder

Abstract: Temperament is a construct that is relatively stable over time but varies between individuals. Research suggests that children with autism spectrum disorder have a ‘reactive’ temperament profile when compared to peers with or without disabilities. However, our understanding of how temperament varies within children with autism and how it relates to child symptoms and outcomes is limited. This study aimed to (a) explore the variation of individual temperament traits within a sample of school-aged child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
0
8
1
Order By: Relevance
“…The findings of this study further emphasize that parenting stress is influenced by the types of child's neurodevelopmental disorder that has to do with the severity of the neurodevelopmental disorders' symptoms which has an impact on the increase of child's maladaptive behaviours (Lee et al 2020). This is also confirmed by several other studies that have proven that the problematic behaviours in children with ASD (Harrop et al 2016, Zaidman-Zait et al 2014, the low adaptive ability of children with ADHD (Peasgood et al 2020), and the increased maladaptive behaviour of children with ID (Giltaij et al 2015) has an impact on maternal parenting stress.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The findings of this study further emphasize that parenting stress is influenced by the types of child's neurodevelopmental disorder that has to do with the severity of the neurodevelopmental disorders' symptoms which has an impact on the increase of child's maladaptive behaviours (Lee et al 2020). This is also confirmed by several other studies that have proven that the problematic behaviours in children with ASD (Harrop et al 2016, Zaidman-Zait et al 2014, the low adaptive ability of children with ADHD (Peasgood et al 2020), and the increased maladaptive behaviour of children with ID (Giltaij et al 2015) has an impact on maternal parenting stress.…”
Section: Discussionmentioning
confidence: 63%
“…This means that the more severe the child's NDD, the lower the mother's perception of the child's adaptive behaviours and the higher the mother's perception of the child's maladaptive behaviours. Previous studies found that the severity of disability relates to the emerging maladaptive behaviours in children with NDD (Lee et al 2020). Other research found that child's characteristics and symptom severity are strongly associated with the experience of parenting stress in mothers of chidren with ASD (Brobst et al 2009, Ekas and Whitman 2010, Estes et al 2009, mothers of chidren with ADHD (Leitch et al 2019), and mothers of chidren with ID (Biswas et al 2015).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They also coalesce in the construct of undercontrol—a clinically significant cluster defined by traits such as impulsivity, inattention, and emotional volatility ( 15 ). A similar cluster characterized by low attentional focusing, low approach tendencies, anger/frustration, and impulsivity was found to predict poor adaptive functioning in children with autism ( 16 ). It is also noteworthy that the combination of negative emotionality, notably anger, and low effortful control was more strongly associated with violent and non-violent delinquency than psychopathic traits and childhood traumatic events in a sample of juvenile offenders ( 5 ).…”
Section: Introductionmentioning
confidence: 90%
“…On average, autistic children demonstrate higher negative affectivity, lower sociability and self-regulation than neurotypical children or children with other diagnoses (Chetcuti et al, 2021). Temperament may signal individual differences in autistic children who have developmental relevance to adaptation, mental health, and well-being outcomes (Chetcuti et al, 2020; Helles et al, 2016), which is supported by increasing longitudinal studies (Chetcuti et al, 2021; Konke et al, 2022; Lee et al, 2020; Narvekar et al, 2022). But there are still many knowledge gaps, especially regarding (1) how variability in temperament reflects and interacts with neurodivergent early-stage sensory-motor processing and later neurocognitive modifiers (e.g.…”
Section: Consider How Autistic/neurodivergent Ways Of Being Shape Per...mentioning
confidence: 97%